Electronic Human Resource Management (e-HRM): A Systematic Review of Benefits, Challenges, and Future Research Directions - Rosalina, Dhian; Nurlaila, Nurlaila; Kamilah, Kamilah (UNIVED Press, 2026)
This study aims to systematically review the development, benefits, challenges, and future research directions in the implementation of Electronic Human Resource Management (e-HRM) in the era of digital transformation. Employing a Systematic Literature Review (SLR) approach guided by PRISMA and bibliometric analysis using VOSviewer and Biblioshiny, the study analyzed 15 empirical articles published between 2019 and 2025 that are indexed in Scopus. The network visualization results reveal that e-HRM serves as a central theme closely linked to issues such as Artificial Intelligence, digital ethics, technostress, corporate sustainability, and organizational performance. The density visualization analysis shows that researchers have extensively explored e-HRM and organizational performance, yet areas such as technostress, digital ethics, and corporate sustainability still represent potential research gaps. Overall, the findings reveal that implementing e-HRM enhances HR process efficiency, enables data-driven decision-making, improves employee experience, and supports organizational sustainability.. Nevertheless, the study also identifies several challenges, such as high implementation costs, resistance to digital transformation, data security and privacy risks, and the emergence of technostress among employees. Based on the review results, future studies should focus on integrating Artificial Intelligence (AI) and machine learning into e-HRM, examining ethical considerations in algorithmic decision-making, and exploring the cross-cultural adaptability of e-HRM systems.